Major Insights in Dynamics of Host Response to SARS-CoV-2: Impacts and Challenges - Hakim, Al; Hasan, Md. Mahbub; Hasan, Mahmudul; Lokman, Syed Mohammad; Azim, Kazi Faizul; Raihan, Topu; Chowdhury, Parveen Afroz; Azad, Abul Kalam (Frontiers in Microbiology, 2021)
COVID-19, a pandemic declared by the World Health Organization on March 11, 2020, is caused by the infection of highly transmissible species of a novel coronavirus called Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). As of July 25, 2021, there are 194,372,584 cases and 4,167,937 deaths with high variability in clinical manifestations, disease burden and post-disease complications among different people around the globe. Overall, the COVID-19 is manifested as mild to moderate in almost 90% cases and only the rest 10% of cases need hospitalization. However, patients with older age and those having different comorbidities have made the worst pandemic scenario. The variability of pathological consequences and clinical manifestations of COVID-19 is associated with differential host-SARS-CoV-2 interactions, which are influenced by the factors originated from the SARS-CoV-2 and the host. These factors usually include the genomic attributes and virulent factors of the SARS-CoV-2, the burden of coinfection with other viruses and bacteria, and age and gender of the individuals, different comorbidities, and immune suppressions/deficiency, genotypes of major histocompatibility complex and blood group antigens and antibodies. We herein retrieved and reviewed literatures from PubMed, Scopus and Google relevant to clinical complications and pathogenesis of COVID-19 among people of different age, sex and geographical locations, genomic characteristics of SARS-CoV-2 including its variants, host response under different variables and comorbidities to summarize the dynamics of the host response to SARS-CoV-2 infection, and host response towards approved vaccines and treatment strategies against COVID-19. After reviewing a large number of published articles covering different aspects of host response to SARS-CoV-2, it is clear that one aspect from one region is not working with the scenario same to others as studies have been done separately with a very small number of cases from a particular area/region of a country. Importantly, to combat such a pandemic as COVID-19, a conclusive understanding of the disease dynamics is required. This review emphases on the identification of the factors influencing the dynamics of host responses to SARS-CoV-2 and offers a future perspective to explore the molecular insights of COVID-19.